National testing : past, present and future / Diane Shorrocks-Taylor. - Shorrocks-Taylor, Diane (Issues in assessment and testing, 1999)
Focusing on the national test for 7, 11 and 14-year-olds, this text provides a discussion on the implications of national testing in England and Wales. It is illustrated with examples of test questions and children's responses.